Evaluasi Ketersediaan Air Baku pada Bendung Gunungcupu - Yulianti, Jihan; Permana, Sulwan; Nugraha, Mochammad Suva (Jurnal Konstruksi, 2023)
The availability of water at Gunungcupu Dam is very much needed to support various community activities in the service area. One of the causes of the reduced supply of clean water is damage to pipes due to natural disasters, such as what happened in 2022, there was a flash flood that overflowed the Citanduy River located in the Gunungcupu Bend area and caused the main raw water transmission pipe belonging to PDAM Tirta Galuh Ciamis to reach the Gunungcupu Intake. cut off for 100 meters, as a result the water supply in the Gunugcupu Dam service area was disrupted. So this research was carried out to determine the availability of raw water, find out the projected need for clean water in 2042, and find out the planned flood discharge at Gunungcupu Dam. The method used is a quantitative approach. To determine the availability of raw water, you need to process actual discharge data using the Weibull equation, calculate population projections using arithmetic and geometric methods, calculate clean water requirements for domestic needs in 2042, and process rainfall data to analyze the planned maximum discharge using the Unit Hydrograph method. Nakayasu Synthetic and Gama I Synthetic Unit Hydrograph. The calculation results show that water availability at the Gunungcupu Dam is 730 liters/second. The need for clean water in 2042 for the three sub-districts is 302.66 liters/second. Based on these results, the water supply from Gunungcupu Dam can meet the clean water needs for Ciamis, Baregbeg, and Cijeungjing Districts in 2042. Then the flood discharge planned by the Nakayasu HSS method for Gumbel probability at Q100 is 930,484 m3/second and for Log Normal probability at Q100 amounting to 786,302 m3/second, while the planned flood discharge for the HSS Gama I method for Gumbel probability in Q100 is 833,381 m3/second and for Log Normal probability in Q100 is 707,002 m3/second. Based on these results, it can be concluded that the largest maximum discharge is the HSS Nakayasu method for Gumbel probability, so the HSS Nakayasu method is good for planning the safety of water structures against flooding.